Ixekizumab-induced interstitial lung disease: a case report confirmed by transbronchial lung cryobiopsy - Shota Kaburaki; Naoko Okada; Toru Tanaka; Koichiro Kamio; Yosuke Tanaka; Yasuhiro Terasaki; Kazuo Kasahara; Masahiro Seike (Journal of Dermatological Treatment)
Background: Ixekizumab, an interleukin-17A (IL-17A) inhibitor used in psoriasis treatment, has been linked to drug-induced interstitial lung disease (DI-ILD). The pathophysiological mechanisms and histopathological features of this adverse effect remain poorly documented.Case Presentation: A 69-year-old male with familial psoriasis developed respiratory symptoms after 18 months of ixekizumab therapy. His medical history included mild smoking-related interstitial pneumonia and chronic obstructive pulmonary disease. One month after treatment, he presented with cough and dyspnea. High-resolution chest CT showed bilateral ground-glass opacities, accompanied by elevated Krebs von den Lungen-6 and surfactant protein-D levels. Transbronchial lung cryobiopsy (TBLC) revealed a fibrotic non-specific interstitial pneumonia pattern with granulomatous changes. Immunohistochemical analysis demonstrated a predominance of CD4-positive cells and IL-17A-positive lymphocytes, suggesting Th17 cell involvement in the pathogenesis. The patient’s condition improved following ixekizumab discontinuation.Conclusions: This case identifies distinct histopathological features in ixekizumab-induced DI-ILD, particularly the presence of granulomatous changes and Th17 cell involvement. The findings suggest that IL-17A inhibition may trigger pulmonary inflammation through Th17 cell function dysregulation. This observation supports the importance of careful pulmonary monitoring in patients receiving biologic therapies for psoriasis, particularly those with pre-existing lung conditions. TBLC may contribute to understanding the pathogenesis of this drug-induced complication.